Hidroloģiskā un ūdens kvalitātes monitoringa atbilstības analīze ES Ūdens struktūrdirektīvas prasībām (Rēzeknes - Maltas upju baseini) - Kudrjavskis, Viktors (Latvijas Universitāte, 2006)
Darbā atspoguļo galvenas problēmas, kas saistīti ar jauno vides monitoringu programmu ieviešanu Latvijā Rēzeknes-Maltas upju baseinu piemērā. Apskatīti ES un Latvijas Republikas likumdošanas prasības ūdeņu aizsardzības jomā. Paskaidroti Rēzeknes-Maltas upju baseinu fiziski ģeogrāfiskie ipašības, antropogēnas slodzes raksturojums. Aprakstīti kādās kriterijas izmantoti jaunu monitoringu staciju vietu izvelei un kādās izmaiņas būs monitoringu stacijas tīklī. Darbā izanalizēti Latvijas hidroķīmiska un hidroloģiska tīkla attistības vēsture, mūsdienu tīkla stāvokli un nākotni. Darbā tika izmantoti materiāli LVĢMA, LVA, daudz internetavotus, kas saistīti ar likumdošanas bāzi. Darbā ir daudz tabulas, grafiku un foto no lauku apsekojumu darbu. Atslēgas vārdi: Ūdens struktūrdirektīva, Rēzeknes-Maltas upju baseini, ŪSD prasības, Vides monitoringa programma 2006

The main problems which are reflected in this reseach work are connected with introduction of the new monitoring programme in Latvia on the basis of the Rezekne-Malta river basin. The EU and Latvian Republic demands of legislation in water resouces protection were observed. Physical geographical peculiarities of the Rezekne-Malta basin and the character of anthropogenic load were revealed. Theoretical part analised the criterions of the selection of the new monitoring stations. There were reseached the changes of the new monitoring waternet. In this work there was analised the history of the hydrochemical and hydrological monitoring net development in Latvia. There were used the materials from Latvian Agencs of Environment, Geology and Meteorology and Latvian Agency of Environment data-base, were used Internet sources which are connected with legislation in this work. There are many charts, tabeles and photomaterials from the visited objects. In practical part there were observed the places of the new monitoring stadions in the Rezekne-Malta rivers basin. During 2005. year there were measured 21 dischares and was calculated the run-off of the Rezekne-Malta river. KEY WORDS: Water framework directive, the Rezekne-Malta rivers basin, WFD peculiarities, Latvian Environment Monitoring Programme 2006.
The Eligibity Analysis of the Hydrological and Water Quality Monitoring to the EU Water Framework Directives Requirements (the Rezekne - Malta Rivers Basins)
Keywords: Vides zinātne